2008
DOI: 10.1097/hjh.0b013e3283060f2e
|View full text |Cite
|
Sign up to set email alerts
|

Prorenin engages the (pro)renin receptor like renin and both ligand activities are unopposed by aliskiren

Abstract: This is the first report demonstrating equal ligand activities of both, renin and prorenin, on the (pro)renin receptor - promyelocytic zinc finger protein-phosphatidylinositol-3 kinase-p85alpha pathway. The failure of aliskiren to inhibit the noncatalytic effects of renin and prorenin may be of clinical relevance considering the increase in plasma concentrations of (pro)renin under aliskiren treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
75
1
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 35 publications
11
75
1
2
Order By: Relevance
“…32 The plasma prorenin levels in diabetic patients were significantly higher than those in non-diabetic patients. Nevertheless, arterial (P)RR expression was similar in diabetic and non-diabetic patients, suggesting that the negative feedback mechanism of the (P)RR observed in cultured cells 26,27 does not work in diabetic patients. In addition, multiple regression analyses showed a significant association with a large coefficient between the arterial mRNA level of the (P)RR and the arterial mRNA level of angiotensin-converting enzyme; this significant association disappeared in patients who had been treated with inhibitors of the renin-angiotensin system.…”
Section: Arterial Mrna Levels In Patients With Stage 5 Chronic Kidneymentioning
confidence: 84%
“…32 The plasma prorenin levels in diabetic patients were significantly higher than those in non-diabetic patients. Nevertheless, arterial (P)RR expression was similar in diabetic and non-diabetic patients, suggesting that the negative feedback mechanism of the (P)RR observed in cultured cells 26,27 does not work in diabetic patients. In addition, multiple regression analyses showed a significant association with a large coefficient between the arterial mRNA level of the (P)RR and the arterial mRNA level of angiotensin-converting enzyme; this significant association disappeared in patients who had been treated with inhibitors of the renin-angiotensin system.…”
Section: Arterial Mrna Levels In Patients With Stage 5 Chronic Kidneymentioning
confidence: 84%
“…Aliskiren does not inhibit binding of (pro)renin to the (P)RR, 87,118 nor does it prevent (pro)renin-induced cell signaling. 87,118,120 However, in STZ-diabetic mRen-2 rats treated with aliskiren for 10 weeks, in situ hybridization on renal sections revealed a clear reduction in gene expression of the (P)RR in the glomeruli and tubular cells compared with vehicle-control diabetic mRen-2 rats. 87 Interestingly, in vitro studies showed that aliskiren did not affect gene expression of (P)RR in mesangial cells.…”
Section: Aliskiren Localizes In the Kidneymentioning
confidence: 91%
“…109 Furthermore, on binding to the (P)RR, prorenin, which is normally inactive, becomes catalytically active (it can cleave Aogen to form Ang I), possibly because of a conformational change induced by the binding. 109,[114][115][116] The Ang IIindependent effects of (P)RR stimulation include activation of extracellular signal-regulated kinase1/2, 109,117,118 and heat shock protein 27 119 and phosphatidylinositol-3 kinase p85a 120 pathways. The production of TGF-b and plasminogen-activator-1 is also increased, as are gene expression and production of collagen I and fibronectin, respectively.…”
Section: Aliskiren Localizes In the Kidneymentioning
confidence: 99%
“…The handle region peptide (HRP), a putative blocker of the (P)RR, could efficiently block glomerulosclerosis, 86,88,95,96 while RAS inhibitors were unable to prevent end-stage organ damage associated with diabetes. 97,98 However, not all investigators were able to reproduce the inhibitory effects of HRP either in vivo or in vitro. 97,99 In diabetic subjects, prorenin to active renin ratio is very high.…”
Section: Implication Of (P)rrs In Pathologic Conditionsmentioning
confidence: 99%